Spatial Mapping of the Distribution of Irrigation Water Discharge on Paddy Fields in Kotabunan District, East Bolaang Mongondow Regency - Chintya Gita Sartika Modeong; Johannes E. X Rogi; Sofia Wantasen (Sam Ratulangi University, 2023)
The research carried out in Kotabunan District, Bolaang Mongondow Timur Regency for 5 (five) months from November 2022 to April 2023 aims to calculate the discharge and distribution of irrigation water discharge flowing to paddy fields in Kotabunan District, East Bolaang Mongondow Regency and to form a map of the distribution of irrigation water discharge. The data used are primary data and secondary data. Primary data, namely data on the depth of irrigation water, water flow velocity, and water discharge by measuring using a current meter every week for six weeks in the morning with three repetitions in the primary irrigation channel 8 (eight) sample points with distance between sample points 500 m, secondary irrigation channels 5 (five) sample points, and tertiary irrigation channels 4 (four) sample points. Furthermore, the data obtained was added to the spatial data to form a spatial map of the distribution of Buyat irrigation water discharge, Kotabunan District, East Bolaang Mongondow Regency. The results showed that the average irrigation water discharge for primary irrigation channels was 0.24 m3/second, secondary irrigation channels were 0.08 m3/second, and tertiary irrigation channels were 0.03 m3/second and the distribution of Buyat irrigation water discharge was uneven so that it affected adequacy, timeliness of meeting the water needs of paddy fields, Kotabunan District, East Bolaang Mongondow Regency. Keywords: Irrigation, water discharge, spatial mapping, rice fields, Kotabunan Abstrak Penelitian yang dilaksanakan di Kecamatan Kotabunan Kabupaten Bolaang Mongondow Timur selama 5 (lima) bulan mulai bulan November 2022 sampai April 2023 bertujuan untuk menghitung debit dan sebaran debit air irigasi yang dialirkan pada lahan sawah Kecamatan Kotabunan Kabupaten Bolaang Mongondow Timur dan terbentuknya peta sebaran debit air irigasi. Data yang digunakan adalah data primer dan data sekunder. Data primer yaitu data kedalaman air irigasi, kecepatan aliran air, serta debit air dengan cara mengukur dengan menggunakan alat current meter setiap minggu selama enam minggu pada pagi hari dengan tiga kali ulangan di saluran irigasi primer 8 (delapan) titik sampel dengan jarak antar titik sampel 500 m, saluran irigasi sekunder 5 (lima) titik sampel, dan saluran irigasi tersier 4 (empat) titik sampel. Selanjutnya data yang diperoleh ditambah dengan data spasial dibut peta spasial sebaran debit air irigasi Buyat Kecamatan Kotabunan Kabupaten Bolaang Mongondow Timur. Hasil penelitian menunjukkan rata-rata debit air irigasi saluran irigasi primer adalah 0,24 m3/detik, saluran irigassi sekunder 0,08 m3/detik dan saluran irigasi tersier 0,03 m3/detik serta sebaran debit air irigasi Buyat penyebarannya tidak merata sehingga mempengaruhi kecukupan, ketepatan waktu pemenuhan kebutuhan air lahan sawah Kecamatan Kotabunan Kabupaten Bolaang Mongondow Timur. Keywords : Irigasi, debit air, pemetaan spasial, sawah, Kotabunan